Azusa Reimagined. A Radical Vision of Religious and Democratic Belonging - Gultom, Junifrius (Kharisma: Jurnal Ilmiah Teologi, 2023)
In Keri Day's examination of the Azusa Street Revival, this abstract captures a nuanced analysis of its historical, theological, and critical dimensions. Day reveals Azusa Street as a radical, counter-cultural space challenging America's racial-capitalist order. The movement's spiritual practices, including speaking in tongues and healing, subverted segregation, offering belonging in an era where it was denied to black individuals. Azusa's critique extended to America's racial-capitalist system, emphasizing egalitarian leadership and gender equality. The study explores Azusa's disruptive impact on the racist and capitalist erotic landscape, highlighting its transformative power. It underscores the movement's dilution in modern Pentecostalism and urges scholars to investigate contemporary experiences within racial capitalism's context, addressing enduring structural racism in the face of emerging neo-capitalism.